Deconstructing Attitudes About Intimate Partner Violence and Bystander Intervention: The Roles of Perpetrator Gender and Severity of Aggression - Ermer, Ashley E. (Journal of interpersonal violence, 2021)
In this mixed methods study, we explored how gender of an aggressor and the levels of aggression (i.e., yelling, throwing a drink, slapping, and punching) influenced attitudes about (a) public displays of intimate partner violence (IPV) and (b) bystander intervention. A feminist-informed, social constructionist perspective guided the study. Participants (N = 562) responded online to randomly assigned factorial vignettes. Participants ranged in age between 18 and 70 years. The majority were female, self-identified as heterosexual, and identified as White. Logistic regressions revealed that participants significantly viewed aggression as unacceptable, especially in cases of more severe and male-perpetrated aggressions. Multinomial logistic regressions revealed that participants significantly thought bystanders or friends of the couple should intervene, especially in cases of male-perpetrated and/or more severe aggression. Analyses of qualitative responses indicated that participants viewed aggression as never okay, as poor communication, as justified if provoked, and discussed the gendered double standard of aggression (i.e., men should not be aggressive because they could cause more harm than females and female-perpetrated aggression is minor, in comparison). Regarding attitudes about bystander intervention, analyses of qualitative responses indicated that aggression severity, issues surrounding relationship privacy, factors relevant to the situation (e.g., if the event occurred once or repeatedly), perceptions that help was needed (e.g., if the victim was hurt), and the bystander’s relationship with the victim (i.e., friend or not) were important to consider when thinking about the decision to intervene in public acts of violence. These findings have implications for bystander intervention programs and for how individuals view public acts of IPV.